THE NECESSITY AND REALITY OF ISLAMIC RELIGIOUS EDUCATION IN SCHOOLS - Amaly, Abdul Mun'im; Herdiana, Yayan; Ruswandi, Uus; Arifin, Bambang Syamsul (Islam Futura, 2023)
Currently, Islamic religious education (PAI) is experiencing various obstacles due to various factors and is considered unable to achieve the expected goals of PAI itself, so that many criticisms are directed at PAI, this study aims to reveal what is criticized from PAI itself, and what steps should be taken to improve existing constraints, using a qualitative approach and literature study methods the researcher collects from various reliable sources about the problems that occur concerning PAI, the results of this study indicate that the spotlight and criticism of PAI include several aspects, namely: PAI learning process is less than optimal, incompetent educators, students who are not pro-active, monotonous learning methods, less varied learning media, and incomplete learning evaluations. These aspects cannot be carried out optimally so that PAI experiences obstacles and setbacks, therefore the improvement and strengthening of these aspects need to be studied to solve problems that occur in PAI.